2016
DOI: 10.5152/dcbybd.2015.955
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Experiences of Patients Discharged from Intensive Care Units

Abstract: Objective: The purpose of this study was to assess the experiences of patients discharged from intensive care units. Material and Methods:This descriptive and cross-sectional study was conducted with 190 patients who were hospitalized in intensive care units for 24 h and over in a university hospital and a public hospital in Manisa, Turkey. Data were collected by a demographic questionnaire and the Intensive Care Experience Scale. Mean±standard deviation, percentage, Pearson correlation coefficient, and Kruska… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
4
0
6
Order By: Relevance
“…The stressors that have been frequently reported in previous studies include sleep deprivation, thirst, gastric tube, oxygen administration, tracheal aspiration, physical movement, isolation, nursing care applications, and inability to speak. 11,15,25,33,34 Each of these stressors was Demir et al 35 The Turkish version consists of 19 items and four subscales, that is, awareness of surroundings (5 items; 5-25 points), frightening experiences (6 items; 6-30 points), recalling of experiences (4 items; 4-20 points), and satisfaction with care (4 items; 4-20 points). In the study by Demir et al, 28 Cronbach's alpha coefficient was found to be .69 for the scale.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stressors that have been frequently reported in previous studies include sleep deprivation, thirst, gastric tube, oxygen administration, tracheal aspiration, physical movement, isolation, nursing care applications, and inability to speak. 11,15,25,33,34 Each of these stressors was Demir et al 35 The Turkish version consists of 19 items and four subscales, that is, awareness of surroundings (5 items; 5-25 points), frightening experiences (6 items; 6-30 points), recalling of experiences (4 items; 4-20 points), and satisfaction with care (4 items; 4-20 points). In the study by Demir et al, 28 Cronbach's alpha coefficient was found to be .69 for the scale.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…They also reported a negative relation between the mental component of the quality of life and ICU experiences and a positive relation between awareness of surroundings, recall of experiences, and satisfaction with care and ICU experiences . It has also been noted in the literature that demographic features, duration of ICU stay, mechanical ventilation, pain, and communication affect the ICU experiences of patients . However, there are insufficient data on the effect of stressors on patients' ICU experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Hintistan ve arkadaşlarının çalışmasında yaş, cinsiyet, eğitim durumu, medeni durum, mesleğin hastaların yoğun bakım deneyimlerini etkilemediği belirlenmiştir. [13] Adsay ve Dedeli'nin çalışmasında [16] kadınların ve yoğun bakımda kalma süresinin 20 gün ve üzerinde olan hastaların yoğun bakım deneyimlerini etkilediği bulunmuştur. [16] Terzi'nin çalışmasında hastalarda cinsiyet, yaş medeni durum, eğitim durumu, meslek ve gelir durumunun yoğun bakım deneyimlerini etkilemediği belirlenmiştir.…”
Section: Hasta Bilgi Formuunclassified
“…[13] Adsay ve Dedeli'nin çalışmasında [16] kadınların ve yoğun bakımda kalma süresinin 20 gün ve üzerinde olan hastaların yoğun bakım deneyimlerini etkilediği bulunmuştur. [16] Terzi'nin çalışmasında hastalarda cinsiyet, yaş medeni durum, eğitim durumu, meslek ve gelir durumunun yoğun bakım deneyimlerini etkilemediği belirlenmiştir. [1] Yaşla birlikte çoklu kronik hastalık varlığı olmakla birlikte hastaların olumlu baş etme mekanizmaları geliştirmelerinin yaşlı hastaların yoğun bakım deneyimlerini olumlu yönde etkilediği düşünülmektedir.…”
Section: Hasta Bilgi Formuunclassified